Conformational dynamics of a hydrophobic prion fragment (113–127) in different pH and osmolyte solutions. (June 2016) - Inayathullah, Mohammed; Rajadas, Jayakumar
Abstract: Prion diseases are characterized by a conformational change in prion protein from its native state into beta-sheet rich aggregates that are neurotoxic. The central domain that contain a highly conserved hydrophobic region of the protein play an important role in the toxicity. The conformation of the proteins is largely influenced by various solvent environments. Here we report results of study of hydrophobic prion fragment peptide PrP(113–127) under different pH and osmolytes solution conditions. The secondary structure and the folding of PrP(113–127) was determined using circular dichroism and fluorescence spectroscopic methods. The results indicate that PrP(113–127) adopts a random coil conformation in aqueous buffer at neutral pH and that converted into beta sheet on aging. Even though the initial random coil conformation was similar in different pH conditions, the acidic as well as basic pH conditions delays the conformational transition to beta sheet. FRET results indicate that the distance between N and C-terminal regions increased on aging due to unfolding by self-assembly of the peptide into an organized beta sheet structure. Presence of osmolytes, prevented or decelerated the aggregation process of PrP(113–127) peptide.